Pelatihan Pengembangan Website Sistem Penjualan Online Berbasis Content Menagement System (CMS) Wordpress - Novalia, Elfina; Hananto, Agustia; Emilia Sukmawati, Cici; Wahyu, Pratama; Voutama, Apriade (VINICHO MEDIA PUBLISINDO, 2024)
This WordPress Content Management System (CMS) based website development training activity is designed to help digitize the helmet washing service business in Karawang. The purpose of this training is to equip business owners with skills in managing online sales platforms to expand market reach and make it easier for customers to order services. The training is carried out offline with a direct practice method, including a basic introduction to WordPress, theme and plugin installation, to optimizing online store features. Based on the evaluation, this training received a participant satisfaction rate of 85%. Participants felt helped by the material provided and were able to practice creating and managing websites independently to support their business operations. This training is expected to be able to increase the competitiveness of the helmet washing business in Karawang by utilizing an effective digital platform to reach customers more widely.